Wavelet Analysis of Shower Track Distribution in High-Energy Nucleus-Nucleus Collisions - Provash Mali; Soumya Sarkar; Amitabha Mukhopadhyay; Gurmukh Singh (Advances in High Energy Physics)
A continuous wavelet analysis is performed for pattern recognition of charged particle emission data in 28Si-Ag/Br interaction at 14.5A GeV and in 32S-Ag/Br interaction at 200A GeV. Making use of the event-wise local maxima present in the scalograms, we try to identify the collective behavior in multiparticle production, if there is any. For the first time, the wavelet results are compared with a model prediction based on the ultrarelativistic quantum molecular dynamics (UrQMD), where we adopt a charge reassignment algorithm to modify the UrQMD events to mimic the Bose-Einstein type of correlation among identical mesons—a feature known to be the most dominating factor responsible for local cluster formation. Statistically significant deviations between the experiment and the simulation are interpreted in terms of nontrivial dynamics of multiparticle production.